Preparation method of a capacitor battery negative electrode with spatial dislocation of electron ion transmission paths
Patent Information
- Application Number
- CN202611317767.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-30
AI Technical Summary
然而,单一多孔集流体主要改善电子接触和局部浸润,单一孔隙梯度主要调节离子通道,亲锂金属层则可能在其暴露位置降低锂成核势垒,难以同步协调面内电子电流和厚度方向锂离子通量
[0035]1、通过泡沫铜与聚丙烯腈基碳布的导电复合,并使碳包覆银纳米颗粒含量从复合集流体侧向隔膜侧递减,可将较强电子汇集和较低锂成核势垒的结构区域限定于复合集流体侧,减轻电子电流集中与隔膜侧锂离子富集在同一区域叠加的风险。
Smart Images

Figure CN123017752A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrochemical energy storage devices and electrode material preparation, and particularly to a method for preparing a capacitor battery negative electrode with spatially misaligned electron-ion transport paths. Background Technology
[0002] Lithium-ion capacitors combine the energy storage characteristics of both battery-type and capacitor-type electrodes. In liquid electrolyte systems, hard carbon anodes typically rely on current collectors to collect electrons and provide thickness-direction transport channels for lithium ions through the pores of the active layer. Under low-temperature and high-rate charging conditions, electrolyte viscosity increases and ion migration rates decrease, making spatial inconsistencies between electron and ion transport within the anode more likely.
[0003] Existing solutions often employ porous current collectors, active layer pore gradients, or lithiophilic metal layers to improve local transport or nucleation behavior. However, a single porous current collector primarily improves electron contact and local wetting, a single pore gradient mainly modulates ion channels, and a lithiophilic metal layer may lower the lithium nucleation barrier at its exposed sites, making it difficult to simultaneously coordinate in-plane electron current and thickness-direction lithium-ion flux. When the lithiophilic metal is exposed on the separator side, it may also cause aberrant lithium to preferentially nucleate on the outer surface of the negative electrode.
[0004] Therefore, there is a need for a method to prepare a capacitor battery anode that can overcome the shortcomings of the existing technology in terms of spatial misalignment of electron-ion transport paths. Summary of the Invention
[0005] One objective of this invention is to propose a method for preparing a capacitor battery negative electrode with spatially misaligned electron-ion transport paths. Addressing the problem in existing technologies where it is difficult to simultaneously adjust the electron and lithium-ion transport paths in hard carbon negative electrodes and the potential for inducing lithium-affinity nucleation on the separator side, this invention proposes a composite current collector composed of copper foam and polyacrylonitrile-based carbon cloth. Three hard carbon slurries with progressively increasing pore-forming agent content and progressively decreasing carbon-coated silver nanoparticle content are layered to form a film. After heat treatment, a three-layer hard carbon active layer is formed with increasing porosity towards the separator side and decreasing silver content towards the separator side. A continuous hard carbon and conductive carbon capping layer is formed on the separator side, without the addition of a silver source in the preparation materials. This invention provides the technical advantages of separating electron-transporting and lithium-ion-transporting regions along the thickness direction of the negative electrode, limiting silver exposure on the separator side, and providing structural conditions for abnormal lithium nucleation into the negative electrode interior or on the current collector side.
[0006] This invention provides a method for preparing a capacitor battery negative electrode with spatially misaligned electron-ion transport paths, comprising:
[0007] S1. Conductive composite of copper foam and polyacrylonitrile-based carbon cloth is formed to create a composite current collector with copper foam as the support and polyacrylonitrile-based carbon cloth as the coating side.
[0008] S2. Prepare the first hard carbon slurry, the second hard carbon slurry and the third hard carbon slurry respectively, so that the content of pore-forming agent in the three hard carbon slurries increases in sequence and the content of carbon-coated silver nanoparticles decreases in sequence, to obtain a component reverse gradient slurry group.
[0009] S3. The component reverse gradient slurry group is coated layer by layer on the polyacrylonitrile-based carbon cloth in the order of the first hard carbon slurry, the second hard carbon slurry and the third hard carbon slurry, and dried respectively to form a three-layer hard carbon precursor layer.
[0010] S4. The three-layer hard carbon precursor layer is heat-treated to decompose the pore-forming agent and form a three-layer hard carbon active layer with increasing porosity and decreasing silver content from the composite current collector side to the diaphragm side.
[0011] S5. A continuous hard carbon and conductive carbon capping layer, in which no silver source is added during the preparation of the raw materials, is formed on the membrane side surface of the three-layer hard carbon active layer, so that the capping layer covers the outer surface of the membrane side of the three-layer hard carbon active layer, thereby obtaining the negative electrode for a liquid electrolyte lithium-ion capacitor.
[0012] Optionally, S1 includes: the thickness of the copper foam is 50-100 μm, the porosity is 60%-80%, and the pore size is 50-200 μm;
[0013] The polyacrylonitrile-based carbon cloth has a thickness of 20-40 μm, a surface density of 30-50 g·m⁻², and a surface resistivity of less than 50 mΩ per square block.
[0014] The conductive composite enables the foamed copper to form a continuous surface contact with the polyacrylonitrile-based carbon cloth.
[0015] Optionally, S2 includes: based on the total mass of the solid components of each hard carbon slurry, the mass percentages of ammonium bicarbonate pore-forming agent in the first hard carbon slurry, the second hard carbon slurry, and the third hard carbon slurry are 5%–9%, 10%–14%, and 15%–20%, respectively;
[0016] The carbon-coated silver nanoparticles accounted for 10%, 5%, and 0–1% of the total mass, respectively.
[0017] Furthermore, the carbon-coated silver nanoparticles include a silver core with a particle size of 30-60 nm and a carbon shell with a thickness of 1-2 nm, wherein the carbon shell coats the silver core and separates the silver core from the liquid electrolyte.
[0018] Optionally, S3 includes: controlling the coating amount of each of the three coatings so that the thickness of each hard carbon active layer formed after the heat treatment in step S4 is 25 to 40 μm.
[0019] Optionally, S4 includes: the heat treatment temperature is 250°C and the holding time is 2 hours;
[0020] The three hard carbon active layers formed by the heat treatment have porosities of 25%–35%, 35%–45%, and 45%–55% respectively, in the order from the composite current collector side to the diaphragm side.
[0021] Optionally, S5 includes: the capping layer is formed of hard carbon and conductive carbon;
[0022] X-ray photoelectron spectroscopy analysis showed that the percentage of silver atoms on the outer surface of the diaphragm side of the capping layer was less than 1 at%;
[0023] Under the same cross-section and the same acquisition conditions, the silver peak counting intensity of the energy dispersive X-ray spectrum was acquired by taking the midpoint of the measured thickness of each of the three hard carbon active layers as the sampling position. The silver peak counting intensity decreased sequentially from the composite current collector side to the diaphragm side.
[0024] Furthermore, the three hard carbon active layers are arranged from the composite current collector side to the membrane side in the order of the first hard carbon active layer, the second hard carbon active layer, and the third hard carbon active layer;
[0025] The first hard carbon active layer is in contact with the polyacrylonitrile-based carbon cloth, and the third hard carbon active layer is in contact with the capping layer;
[0026] The silver content of the first hard carbon active layer, the second hard carbon active layer and the third hard carbon active layer decreases sequentially and the porosity increases sequentially.
[0027] Furthermore, it also includes pre-lithiating the anode at -10 to 25°C and 0.05 to 0.2C, using the design capacity of the anode to be pre-lithiated as the 1C capacity reference.
[0028] A pre-lithiation test was conducted using a negative electrode with the same three-layer slurry solid composition, layer thickness, and heat treatment conditions as the negative electrode to be pre-lithiated. The impedance change plateau segment was determined from the 1kHz AC impedance time series data of the pre-lithiation test. The upper limit of the continuous change rate within the impedance change plateau segment was determined as the impedance change rate threshold, and the shortest continuous sampling duration where the continuous change rate does not exceed the upper limit was determined as the predetermined sampling period.
[0029] The common endpoint for terminating pre-lithiation is when the potential of the negative electrode relative to the lithium metal reference electrode enters the range of 0.15 to 0.30V, and the continuous rate of change of the 1kHz AC impedance is not greater than the impedance change rate threshold and continues for the predetermined sampling period.
[0030] The continuous rate of change is determined by the absolute value of the difference between the 1kHz AC impedance amplitudes at adjacent sampling times, the 1kHz AC impedance amplitude at the previous sampling time, and the sampling time interval.
[0031] Furthermore, interlocking acceptance is performed on the same batch of negative electrodes and a batch acceptance record is generated. Only when all three conditions are met—that the porosity of the three-layer hard carbon active layer increases sequentially from the composite current collector side to the diaphragm side, that the silver peak counting intensity decreases sequentially from the composite current collector side to the diaphragm side, and that the percentage of silver atoms on the outer surface of the diaphragm side of the sealing layer is less than 1 at%—are valid test results are written in the batch acceptance record and the batch of negative electrodes is allowed to enter the capacitor assembly process.
[0032] If any condition is not met, the test result is missing, or the test result is invalid, an abnormal status is written into the batch acceptance record and the negative electrode of that batch is stopped from entering the capacitor assembly process.
[0033] After re-testing the items corresponding to the abnormal status, the abnormal status will be lifted only when all three conditions are met and all valid test results are obtained.
[0034] The beneficial effects of this invention are:
[0035] 1. By combining copper foam with polyacrylonitrile-based carbon cloth in a conductive composite, and by decreasing the content of carbon-coated silver nanoparticles from the composite current collector side to the separator side, the structural region with strong electron collection and low lithium nucleation barrier can be confined to the composite current collector side, thereby reducing the risk of electron current concentration and lithium ion enrichment on the separator side overlapping in the same region.
[0036] 2. By increasing the porosity of the three-layer hard carbon active layer from the composite current collector side to the separator side, more sufficient electrolyte wetting and lithium-ion transport space can be provided near the separator, forming a gradient opposite to the direction of decreasing silver content, thus structurally achieving a thickness misalignment between the two types of high-throughput regions.
[0037] 3. By setting a continuous hard carbon and conductive carbon capping layer on the diaphragm side without adding silver source in the raw materials, and combining batch interlocking acceptance of surface silver content, cross-sectional silver gradient and layered porosity, the exposure of lithium-loving silver on the diaphragm side can be reduced, and the gradient structure of the negative electrode can be uniformly constrained before entering the assembly process. Attached Figure Description
[0038] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used in conjunction with embodiments of the invention to explain the invention and do not constitute a limitation thereof. In the drawings:
[0039] Figure 1 This is a flowchart of a method for preparing a capacitor battery negative electrode with spatially misaligned electron-ion transport paths according to the present invention.
[0040] Figure 2This is a flowchart of the process for forming the capping layer and interlocking acceptance in step S5 of the present invention. Detailed Implementation
[0041] The present invention will now be described in further detail with reference to the accompanying drawings. These drawings are simplified schematic diagrams, illustrating only the basic structure of the invention, and therefore only show the components relevant to the invention.
[0042] refer to Figures 1-2 A method for preparing a capacitor battery negative electrode with spatially misaligned electron-ion transport paths, comprising:
[0043] S1. Conductive composite of copper foam and polyacrylonitrile-based carbon cloth is formed to form a composite current collector with copper foam as the support and polyacrylonitrile-based carbon cloth as the coating side.
[0044] S2. Prepare the first hard carbon slurry, the second hard carbon slurry and the third hard carbon slurry respectively, so that the content of pore-forming agent in the three hard carbon slurries increases in sequence and the content of carbon-coated silver nanoparticles decreases in sequence, to obtain a component reverse gradient slurry group.
[0045] S3. The component reverse gradient slurry group is coated layer by layer on the polyacrylonitrile-based carbon cloth in the order of the first hard carbon slurry, the second hard carbon slurry and the third hard carbon slurry, and dried respectively to form a three-layer hard carbon precursor layer.
[0046] S4. The three-layer hard carbon precursor layer is heat-treated to decompose the pore-forming agent and form a three-layer hard carbon active layer with increasing porosity and decreasing silver content from the composite current collector side to the diaphragm side.
[0047] S5. A continuous hard carbon and conductive carbon capping layer, in which no silver source is added during the preparation of the raw materials, is formed on the membrane side surface of the three-layer hard carbon active layer, so that the capping layer covers the outer surface of the membrane side of the three-layer hard carbon active layer, thereby obtaining the negative electrode for a liquid electrolyte lithium-ion capacitor.
[0048] In this specific embodiment, S1 includes:
[0049] In this specific embodiment, a composite current collector is prepared using sheet-like foamed copper (batch number L2026-01) and polyacrylonitrile-based carbon cloth. The foamed copper has a thickness of 75 μm, a porosity of 70%, and an average pore size of 100 μm. The polyacrylonitrile-based carbon cloth has a thickness of 30 μm, a surface density of 40 g·m⁻², and a surface resistivity of 35 mΩ per block. The thickness, porosity, pore size, surface density, and surface resistivity of the incoming materials are recorded in batches. If any of the indicators exceed the range defined in claim 2, the roll of material is isolated and the composite process is stopped.
[0050] Before lamination, the foamed copper was cut into continuous strips 100 mm wide, ultrasonically cleaned with anhydrous ethanol for 10 min, and vacuum dried at 80℃ for 30 min. Then, residual particles were blown away from both sides of the foamed copper with compressed air at 0.1 MPa. The polyacrylonitrile-based carbon cloth was cut with the same width and vacuum dried at 120℃ for 2 h, so that when the two strips entered the lamination station, there were no visible particles on the surface and the moisture content of the carbon cloth was not higher than 0.2 wt%.
[0051] An aqueous conductive adhesive layer composed of conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber is applied between copper foam and polyacrylonitrile-based carbon cloth. The three components are mixed in a solid mass ratio of 70:10:20. The dry surface density of the conductive adhesive layer is controlled to be 2.0 g·m⁻². It is continuously coated on the side of the copper foam facing the carbon cloth using a 120-mesh gravure roller, and the coating is made to penetrate the pores of the copper foam surface without penetrating the thickness of the copper foam.
[0052] Polyacrylonitrile-based carbon cloth is covered on the conductive adhesive layer that is not completely dry. The carbon cloth side is used as the subsequent coating side. Hot roller lamination is carried out at 90°C, linear pressure of 2.0 kN·m⁻¹ and linear speed of 0.5 m·min⁻¹. Then, it is vacuum dried at 100°C for 4 hours. During lamination, edge positioning marks are used to keep the direction of the foam copper side and the carbon cloth side consistent. The batch record of the composite current collector is written with the roll number, start and end meters and the orientation of the carbon cloth side.
[0053] The construction rule of the composite current collector is to first form discrete anchor points with the conductive adhesive layer in the wall of the foamed copper hole, and then connect the lower surface of the polyacrylonitrile-based carbon cloth with each anchor point to form a continuous conductive contact surface through the pressure of the hot roller. The process camera acquires three cross-sectional images with a pixel size of 5μm. The proportion of the contact length between the foamed copper and the carbon cloth that is not separated by contact areas to the total length of the interface is taken as the continuous contact ratio. This ratio should not be less than 95%, and the length of a single uncontacted area along the interface direction should be less than 1mm. The generation criterion is used to exclude composite strips that only have local point contact and cannot continuously merge current.
[0054] To control the consistency of the width direction, tension measuring rollers are set at the inlet, middle and outlet of the hot roll. The tension of the foamed copper is maintained at 18±2N and the tension of the polyacrylonitrile-based carbon cloth is maintained at 12±2N. When the edge deviation of the two strips exceeds 0.5mm, the lamination is automatically stopped and the deviation section is written into the isolation list. When production resumes, the effective starting point is re-established from the first meter mark that simultaneously meets the tension and edge position conditions after the deviation section.
[0055] Cut one 20mm×20mm sample from the beginning, middle and end of the composite strip. Use a four-probe tester to test the surface resistance of the carbon cloth and the DC voltage drop method to test the surface contact resistance from the foamed copper to the carbon cloth. Apply a constant pressure of 0.10MPa to the test fixture. Select five test points for each sample, including the center and four corners. The surface resistance of the carbon cloth should be less than 50mΩ per square. Each test point should have a stable conduction value and the surface contact resistance should not be greater than 50mΩ. This absolute upper limit is determined by the allowable interface voltage drop of no more than 5mV under a target detection current of 100mA. The peeled section should not show continuous delamination with a length exceeding 1mm when observed by an optical microscope.
[0056] The electrical verification of continuous conductive contact was carried out by applying a constant current of 100mA between the back of the foamed copper and the front of the carbon cloth. After each measuring point was held for 5 seconds, the stable voltage was read. The stable voltage drop of the fifteen measuring points was not greater than 5mV, the converted contact resistance was not greater than 50mΩ, and the contact resistance range was not greater than 20% of its average value. A 180° peel test was carried out on three samples with a peel speed of 50mm·min⁻¹ and an average peel strength of not less than 0.8N·cm⁻¹. The samples were released only when the upper limit of absolute contact resistance, the ratio of contact resistance range, the peel strength, and the continuous delamination length were all met. If any result was not met, the corresponding volume number was marked as a composite failure, switched to the isolation storage location, and prohibited from entering the slurry coating.
[0057] The strip that meets the above testing conditions is registered as a composite current collector object. Its structural orientation field is recorded as from the foamed copper support side to the polyacrylonitrile-based carbon cloth coating side. Subsequently, S2 uses the batch record to determine the slurry preparation amount. S3 only forms three hard carbon precursor layers on the polyacrylonitrile-based carbon cloth coating side in sequence, so that the foamed copper and the polyacrylonitrile-based carbon cloth maintain continuous surface contact and provide a continuous electron collection path.
[0058] In this specific embodiment, S2 includes:
[0059] Based on the effective coating area of the composite current collector obtained in S1, the first hard carbon slurry, the second hard carbon slurry, and the third hard carbon slurry were prepared. The three slurries used the same batch of hard carbon powder with a median particle size of 6.5 μm, conductive carbon black with a BET specific surface area of 62 m²·g⁻¹, sodium carboxymethyl cellulose, and styrene-butadiene rubber. The solvent was deionized water with a resistivity of not less than 15 MΩ·cm. The solid mass fraction of each slurry was controlled at 40 wt% to avoid changes in the interlayer shrinkage direction caused by differences in the solvent system.
[0060] The three slurries, based on their respective total solid components by mass of 100%, consist of the following: the first hard carbon slurry, which comprises 73 wt% hard carbon, 4 wt% conductive carbon black, 2 wt% sodium carboxymethyl cellulose, 4 wt% styrene-butadiene rubber, 7 wt% ammonium bicarbonate pore-forming agent, and 10 wt% carbon-coated silver nanoparticles; the second hard carbon slurry, which comprises 73 wt% hard carbon, 4 wt% conductive carbon black, 2 wt% sodium carboxymethyl cellulose, 4 wt% styrene-butadiene rubber, 12 wt% ammonium bicarbonate pore-forming agent, and 5 wt% carbon-coated silver nanoparticles; and the third hard carbon slurry, which comprises 71.5 wt% hard carbon, 4 wt% conductive carbon black, 2 wt% sodium carboxymethyl cellulose, 4 wt% styrene-butadiene rubber, 18 wt% ammonium bicarbonate pore-forming agent, and 0.5 wt% carbon-coated silver nanoparticles.
[0061] The feed mass of each solid component is as follows Verification, The symbol represents the first The first type of hard carbon slurry The mass percentage of each solid component, in %. The symbol represents the first The first type of hard carbon slurry The mass of each solid component fed, in grams. The symbol represents the first The first type of hard carbon slurry The mass of each solid component obtained from the same weighing record, in grams. The symbol represents the index of the discrete component participating in the summation of the total mass of the solids, ranging from 1 to... Furthermore, because it is only used to identify the order of components and the units are not applicable, The symbol represents the total number of solid components in the slurry, and in this specific embodiment, it is taken as 6. This is a discrete count and is dimensionless. The symbol represents the index of the discrete solid component being checked, ranging from 1 to... Furthermore, because it is only used to identify the order of components and the units are not applicable, The symbols represent discrete slurry indices and are sequentially assigned to 1, 2, and 3. Since they are only used to identify the order of slurries and the units are not applicable, the feeding system only allows mixing when the sum of the mass percentages of the solid components of the three slurries is 100%.
[0062] Ammonium bicarbonate pore-forming agent uses powder with a median volume particle size of 8 μm and a purity of not less than 99.0%. Before use, it is equilibrated to room temperature in a sealed desiccator. Carbon-coated silver nanoparticles use powder from the same batch with a nominal silver core particle size of 45 nm and a nominal continuous carbon shell thickness of 1.5 nm. Transmission electron microscopy is used to randomly select no less than 100 particles from each batch to count the silver core particle size and carbon shell thickness. The 10% to 90% percentile of the silver core particle size should be in the range of 30 to 60 nm and the 10% to 90% percentile of the carbon shell thickness should be in the range of 1 to 2 nm.
[0063] Before feeding, carbon-coated silver nanoparticles are pre-dispersed in deionized water at twice the mass of conductive carbon black. They are first stirred at 800 r·min⁻¹ for 10 min, and then ultrasonically dispersed at 20 kHz for 15 min. After centrifugation, no bare silver cores should be observed in the dispersion. The carbon shell serves as an isolation interface between the silver cores and the subsequent liquid electrolyte. Particle batches, silver core statistics, and carbon shell statistics are recorded in the silver source material record. Particles that do not meet the particle size or shell thickness range are not allowed to enter the three types of slurries.
[0064] Before preparing the three types of slurry, the mixing tank, rotor, and sampler were cleaned in the order of the first, second, and third slurries. First, deionized water was circulated for 10 minutes. Then, the surfaces in contact with the slurry were wiped with a lint-free cloth and the last rinse liquid was collected. The cleaning was considered qualified when the difference between the conductivity of the last rinse liquid and that of fresh deionized water was not higher than 5 μS·cm⁻¹ and the silver ion rapid test paper showed no color development. Before preparing the third hard carbon slurry with a lower silver content, the filter screen and delivery hose were replaced to eliminate the gradient reversal caused by the residue of the previous high silver slurry.
[0065] Hard carbon powder and conductive carbon black were vacuum dried at 120℃ for 4 hours and then sealed and cooled. Sodium carboxymethyl cellulose and styrene-butadiene rubber were checked for solid content according to the supply batch number. Ammonium bicarbonate was packaged in 500g bags and fed within 2 hours after opening. The weighing equipment had a range of 0-5kg and a scale value of 0.1g and was calibrated daily with a first-class weight. If the weighing deviation of a single component exceeded 0.2% of the target mass, the weighing was discarded and the material was taken again to avoid masking the weighing deviation by adding other components.
[0066] During the preparation of the slurry, sodium carboxymethyl cellulose is first added to deionized water and stirred at 600 r·min⁻¹ for 60 min to form a homogeneous slurry. Then, hard carbon and conductive carbon black are added and dispersed at 1200 r·min⁻¹ for 30 min. Subsequently, the corresponding carbon-coated silver nanoparticle dispersion is added and mixed at 800 r·min⁻¹ for 20 min. Finally, styrene-butadiene rubber and ammonium bicarbonate are added at 400 r·min⁻¹ and stirring is continued for 15 min. This sequence ensures that ammonium bicarbonate is added at the end of the low-shear stage to limit particle breakage.
[0067] The three slurries were vacuum degassed in a sealed container at 25℃ for 20 min. The viscosity measured by a rotor viscometer at 25℃ and a shear rate of 10 s⁻¹ was controlled between 2.0 and 3.5 Pa·s. The absence of agglomerates larger than 50 μm was confirmed by a 100 μm scraper fineness gauge. If the viscosity was higher than the upper limit, deionized water was added at a ratio not exceeding 0.5% of the total mass of the slurry each time and degassed again. If the viscosity was lower than the lower limit or if unremovable agglomerates appeared, the corresponding slurry was marked as unqualified and not mixed with other slurries.
[0068] The construction rule for the component reverse gradient slurry group is to establish an associated object by taking the three qualified slurry records corresponding to the same composite current collector batch in ascending order of slurry serial number, and at the same time verify that the mass ratio of pore-forming agent satisfies that the first slurry is less than the second slurry and the second slurry is less than the third slurry, and the mass ratio of carbon-coated silver nanoparticles satisfies that the first slurry is greater than the second slurry and the second slurry is greater than the third slurry. If any comparison relationship is not valid, the record is missing, or the preparation time difference exceeds 4 hours, no gradient group number will be generated.
[0069] When two or more candidate feed tanks have the same slurry serial number, the controller first deletes feed tanks that do not meet the conditions for solid mass fraction, viscosity or fineness, and then selects the feed tank with the earliest preparation time and has not exceeded the 8-hour usage time limit. If the preparation time is the same, the one with the smaller absolute value of the quality verification deviation is selected. If they are still tied after comparison, the automatic selection is stopped and the verification personnel determine the unique feed tank based on the original weighing record, thereby preventing the same layer from being associated with two batches at the same time.
[0070] The temperature of the three slurries was maintained at 25±2℃ during preparation, degassing and waiting for coating. The feed tank was stirred at a low speed of 60r·min⁻¹ to prevent the hard carbon and carbon-coated silver nanoparticles from settling. Every 2 hours, a sample was taken from the top and bottom of the tank to determine the solid mass fraction. If the absolute difference between the results of the top and bottom was not greater than 0.5 percentage points, the tank could continue to be used. If the difference exceeded this value, the tank was stirred again at 300r·min⁻¹ for 10 minutes and the result was retested. If the result was still not satisfactory after the second retest, the qualified status of the feed tank was cancelled.
[0071] After the gradient group number is generated, the slurry controller takes 10g of sample from each of the three feeding tanks and dries it to constant weight at 105℃. The solid mass fraction is checked according to the drying quality, and each sample is divided into three parts to determine the weight loss characteristics of ammonium bicarbonate and the mass response of silver. When the relative standard deviation of the three results is not greater than 5% and the sorting direction is consistent with the feeding record, the formula version of that group is locked. The test results are only used to confirm the feeding and mixing uniformity and do not replace the mass ratio of the components described in the claims.
[0072] After the inspection is completed, the three types of slurries are loaded into sealed feeding tanks with independent numbers. The fields of the feeding tanks record the slurry serial number, solid mass fraction, ammonium bicarbonate mass ratio, carbon-coated silver nanoparticle mass ratio, viscosity, preparation time and corresponding composite current collector batch number. An 80-mesh filter screen is installed at the tank outlet. The feeding pipeline of the third hard carbon slurry uses an independent pipeline that has been rinsed with blank water and the silver test paper result is negative, in order to avoid high silver slurry residue entering the diaphragm side layer.
[0073] Three qualified feed tanks together constitute a reverse gradient slurry group, with the ammonium bicarbonate content increasing sequentially from 7wt%, 12wt%, and 18wt%, and the carbon-coated silver nanoparticle content decreasing sequentially from 10wt%, 5wt%, and 0.5wt%. The slurry number and the content fields are transmitted to the layer coating control record in S3 to ensure that the subsequent coating sequence corresponds one-to-one with the reverse gradient components.
[0074] In this specific embodiment, S3 includes:
[0075] S3 reads the composite current collector direction field of S1 and the three feed tank numbers of S2, loads the composite current collector with the foam copper support side facing the conveyor roller and the polyacrylonitrile-based carbon cloth coating side facing the slit die head, and sequentially defines the first hard carbon slurry, the second hard carbon slurry and the third hard carbon slurry as the first, second and third coating tasks. If any feed tank number, slurry number or strip orientation is inconsistent, the controller locks the feed pump.
[0076] Before coating, a correlation was established between the wet coating surface density and the layer thickness after heat treatment using calibration specimens with the same solid composition as the formal slurry. The target dry surface densities for the three coating tasks were set at 33 g·m⁻², 29 g·m⁻², and 25 g·m⁻², respectively, with a slurry solids mass fraction of 0.40. The wet coating surface density was calculated according to... Sure, The symbol represents the first The surface density of the wet slurry applied in the first coat, expressed in g·m⁻². The symbol represents the first The target dry solids surface density for the first coating is expressed in g·m⁻². The symbol represents the first The solid mass fraction of the seed slurry is dimensionless. The symbol represents the coating layer number and is 1, 2, 3. It belongs to the discrete coating layer sequence index and the unit is not applicable because it is only used to identify the layer sequence.
[0077] The first hard carbon slurry is applied to polyacrylonitrile-based carbon cloth at a linear velocity of 0.5 m·min⁻¹ through a slit die. The gap between the die and the carbon cloth is set to 150 μm. The online weighing module adjusts the feed pump speed according to the target wet coating surface density of 82.5 g·m⁻². The coating passes through two low-temperature hot air zones of 35°C and 45°C for 10 min each, and then dries in a vacuum environment at 45°C until the moisture content of the exit zone is less than 1.0 wt% and the surface remains continuous. The temperature is lower than the significant decomposition initiation temperature confirmed by thermogravimetric analysis of the same batch of ammonium bicarbonate. The result is a first hard carbon precursor layer that is in direct contact with the carbon cloth and retains the pore-forming agent.
[0078] Before each coating task begins, the volumetric flow rate of the feed pump is calibrated with deionized water at five rotation speed points, and the mass flow rate is calculated in combination with the corresponding slurry density. The controller reads the strip speed and online weighing increment every 2 seconds. The feed pump speed is adjusted according to the deviation between the measured wet coating surface density and the target value. If the absolute value of the deviation does not exceed 3%, the current speed is maintained. If it exceeds 3% for five consecutive times, the linear speed is reduced to 0.3 m·min⁻¹ and re-converged. If it still does not recover, the coating of that layer is stopped and the affected section is marked.
[0079] The second hard carbon slurry is applied without leaving the same conveying reference as the first hard carbon precursor layer. The target wet coating surface density is 72.5 g·m⁻². The same linear speed and low temperature segmented drying conditions of 35℃ and 45℃ are used. The starting point of the second coating layer is moved 10 mm behind the starting point of the first layer and the stepped section sampling area is marked in the batch record. After drying, a non-contact thickness gauge is used to sample every 20 mm along the width direction. When three consecutive measuring points deviate from the target dry thickness by more than ±5%, the coating is suspended and the corresponding length of strip is isolated.
[0080] The third hard carbon slurry is coated on the second hard carbon precursor layer at a target wet coating density of 62.5 g·m⁻². The third layer uses the independent feeding pipeline and new filter screen described in S2. After coating, it is dried by low temperature hot air at 35°C and 45°C in sequence, and then dried in a vacuum environment at 45°C for 8 hours until the mass change of the strip in two consecutive weighings does not exceed 0.2%, thereby forming a three-layer hard carbon precursor layer in which the first, second and third hard carbon precursor layers are arranged in sequence from the foam copper support side to the future diaphragm side.
[0081] The second and third coatings are only initiated when the surface temperature of the previous layer drops below 35°C, the residual moisture content is below 1.0wt%, and there is no continuous powdering zone after the 180° tape is removed. The gap between the slit die head and the surface of the previous layer is compensated based on the online thickness measurement results. The compensation amount is equal to the deviation of the actual thickness of the previous layer from the calibrated thickness and is limited to ±10μm. This ensures that the coating is applied layer by layer without scratching the previous layer or mixing adjacent slurries in a undried state.
[0082] After each coating process, a witness strip is left at the edge of the strip that does not enter the finished product area. Simultaneously, single-layer quality witness sheets containing only the first, second, or third slurry are prepared on the same batch of polyacrylonitrile-based carbon cloth according to the corresponding areal density. Cross-sectional microscopic observation is used to confirm that the interfaces between adjacent layers of the formal strip are continuous and that no visible mixing occurs. The areal density is checked three times using the unit area weighing results. One piece is cut from each single-layer quality witness sheet for thermogravimetric analysis. The weight loss in the 60-120℃ range is compared with the theoretical feed mass of ammonium bicarbonate for that layer. The residual amount of ammonium bicarbonate before entering S4 should not be less than 85% of the theoretical feed mass. If the residual amount is insufficient, the density deviation of any layer exceeds the target value ±5%, or there are bubbles, interlayer cracks, mixing, exposed substrate, or through pinholes with a width greater than 0.5mm, the corresponding section is marked as unqualified and prohibited from entering S4.
[0083] The record objects for a qualified three-layer hard carbon precursor layer include the batch number of the composite current collector, the batch numbers of the three slurries, the surface density of the three wet coatings, the surface density of the three dryings, the drying temperature curve, and the sampling location of the stepped section. The target thickness of each layer after S4 heat treatment is set as 30 μm for the first layer, 32 μm for the second layer, and 34 μm for the third layer. All three target values are within the range of 25 to 40 μm. The record objects are transferred to S4 along with the strip as the basis for heat treatment and layer thickness acceptance.
[0084] In this specific embodiment, S4 includes:
[0085] The three-layer hard carbon precursor layer obtained from S3 is cut into 80mm×120mm sheets with orientation marks. No more than 20 sheets per layer are loaded into a heat treatment furnace with a nitrogen inlet and a tail gas absorption unit. The sheets are placed flat on an inert alumina support plate with the copper foam side down and a 2mm gap between adjacent sheets. After the furnace door is closed, the furnace is purged with nitrogen with a purity of not less than 99.999% for 30 minutes to make the oxygen content in the furnace less than 100ppm.
[0086] The heat treatment process involves raising the temperature from room temperature to 120°C at 2°C·min⁻¹ and holding it for 30 min to remove residual moisture, then raising it to 250°C at 1°C·min⁻¹ and holding it for 2 h. During the holding period, the nitrogen flow rate is maintained at 200 mL·min⁻¹. Subsequently, the temperature is naturally cooled to below 60°C under nitrogen protection before being removed from the furnace. Ammonium bicarbonate decomposes during the heating process and is carried out by continuous nitrogen. The tail gas is treated sequentially through a condenser and a weak acid absorption bottle.
[0087] For each furnace, place one witness sheet from the same batch at each of the top, middle, and bottom positions and record the measured temperature curve. During the 250℃ heat preservation stage, the temperature at each measuring point should be maintained at 250±3℃ and the continuous heat preservation time should reach 120min. If any measuring point exceeds this temperature range for more than 5min or the nitrogen flow rate is less than 180mL·min⁻¹, the sheet from that furnace will enter the area to be reviewed and will not directly form a qualified batch.
[0088] After heat treatment, the witness sheet is cold-mounted with resin and ground and polished along the thickness direction. The interlayer boundary is determined by the difference in composition between adjacent layers on the same cross section. The thickness of each layer is measured at five equidistant positions along the width direction and the average value is taken. The average thickness of the first, second and third hard carbon active layers is controlled to be 30±3μm, 32±3μm and 34±3μm respectively, and all measurement points of each layer are kept in the range of 25 to 40μm.
[0089] The formation rule for the three-layer hard carbon active layer is to complete the decomposition of the pore-forming agent in the first, second, and third precursor layers without inverting the original interlayer boundaries. The mass difference of the witness sheet before and after heat treatment is used to confirm that the volatile pore-forming components have been discharged. If the mass change of the witness sheet after two consecutive 30-minute heat treatments is less than 0.3%, the decomposition endpoint is considered valid. If the mass change still reaches or exceeds 0.3%, nitrogen protection is maintained, heat treatment is added, and the sample is weighed again. If the total heat treatment time exceeds 60 minutes and the endpoint is still not reached, the furnace is treated as an abnormal furnace.
[0090] Cross-sectional images were used to establish layer boundary mappings in the order of foamed copper, polyacrylonitrile-based carbon cloth, first hard carbon active layer, second hard carbon active layer, and third hard carbon active layer. Image analysis software performed binary segmentation of the pore area in each layer and cross-verified the results with the porosity results from the volumetric density method. The volumetric density method used three single-layer quality witness sheets prepared simultaneously in S3. Each witness sheet was heat-treated in the same furnace and at the same position as the final sheet. After cooling, the effective coating area and the corresponding average thickness of the single layer were measured to obtain the measured volume. Then, the mass of the blank carbon cloth after being treated in the same furnace was subtracted to obtain the final volume. The dried mass of this layer after heat treatment, with a balance graduation value of 0.01 mg, and the difference in repeated measurements of single-layer mass not exceeding 0.2%, and the deviation of single-layer thickness and unit area weight loss from the corresponding results of the formal three-layer sheet stepped area not exceeding 5%, can be used for the calculation of the bulk density of this layer. When the absolute difference between the image method and the bulk density method is not greater than 5 percentage points, the bulk density method result is retained as the batch value. If the absolute difference exceeds 5 percentage points, a new sample is prepared to exclude invalid measurements caused by grinding and polishing dragging, insufficient resin impregnation, incorrect layer boundary identification, or mismatch of single-layer witness sheets.
[0091] The same direction marking and stepped section sampling area are used before and after heat treatment. After the sheet comes out of the furnace, it is left to stand in an anhydrous drying oven for 30 minutes before being transferred to a sealed bag. The relative humidity inside the sealed bag is controlled to be less than 10%. Each bag contains only sheets from the same furnace and in the same direction. Sheets with missing direction markings, unconfirmed layer boundary sequence, or through cracks on the surface after heat treatment are recorded in the rejection record.
[0092] Porosity of each layer according to calculate, The symbol represents the first Porosity of the hard carbon active layer, in %. The symbol represents the first The bulk density of the hard carbon active layer is determined by the measured volume of the cross-section and the dry mass, in g·cm⁻³. The symbol represents the first The skeletal density of the layered scraped powder, measured by helium displacement method, is expressed in g·cm⁻³. The symbols represent the layer numbers arranged from the composite current collector side to the diaphragm side, and are taken as 1, 2, 3. They belong to the discrete hard carbon active sequence index, and since they are only used to identify the sequence, the units are not applicable. Each density is measured using three parallel witness plates and a Grubbs test is performed at a significance level of 0.05. At most one outlier is removed from each group, and the number of valid parallels after removal must not be less than 2. If there are fewer than 2, the result of this item is invalid and three witness plates are prepared again.
[0093] In this specific implementation, the porosity acceptance ranges for the first, second, and third hard carbon active layers are set to 25%–35%, 35%–45%, and 45%–55%, respectively. The average measured values of the three layers in representative batches are 30.2%, 40.1%, and 50.3%, respectively. The porosity gradient is recorded as valid only when the three results are valid and strictly increase sequentially from the composite current collector side to the diaphragm side. Sheets that do not meet the range or sequence requirements are isolated in the entire batch and feedback is provided to adjust the pore-forming agent dosage or coating density of the corresponding slurry in subsequent batches.
[0094] Each batch of sheets is divided into three sampling levels: upper, middle, and lower, according to their position in the furnace. Three finished products are randomly selected from each level for thickness and porosity verification. If the porosity of any layer of the nine finished products exceeds the corresponding range, the verification is expanded to all the witnessed sheets in the furnace. If the expanded verification still exceeds the limit, the entire furnace is judged to have abnormal pore structure. Only when all nine sheets meet the requirements and the average porosity range of the same layer in the three levels does not exceed 5 percentage points can the pore gradient of the furnace be validly recorded.
[0095] Since the proportions of carbon-coated silver nanoparticles used in the three precursor layers are 10wt%, 5wt%, and 0.5wt% respectively, and the heat treatment at 250℃ is carried out in nitrogen without introducing new silver sources, the first, second, and third hard carbon active layers maintain the material source relationship of decreasing silver content after heat treatment. The first hard carbon active layer remains in contact with the polyacrylonitrile-based carbon cloth, and the third hard carbon active layer is reserved as the bearing surface of the subsequent capping layer.
[0096] The heat treatment qualification record is written with furnace number, temperature curve, nitrogen flow rate, three-layer thickness, three-layer bulk density, three-layer skeleton density and three-layer porosity. The porosity of the three-layer hard carbon active layer increases sequentially from the composite current collector side to the diaphragm side and the silver content decreases sequentially. The direction mark, cross-sectional sampling area and porosity data are then transmitted to the S5 capping, silver gradient detection and batch interlocking acceptance.
[0097] In this specific embodiment, S5 includes:
[0098] S5 uses the third hard carbon active layer obtained in S4 as the capping surface, and separately prepares a capping slurry without adding silver source. The capping slurry is composed of 90wt% hard carbon from the same batch, 4wt% conductive carbon black, 2wt% sodium carboxymethyl cellulose and 4wt% styrene-butadiene rubber by weight of solid components. It is adjusted to 35wt% solid mass fraction with deionized water. Before use, the slurry container, stirring paddle, filter screen and conveying pipeline are checked for silver element with blank wiping sample and confirmed that no silver is detected.
[0099] After degassing at 300 r·min⁻¹ for 15 min, the sealing slurry was continuously coated onto the surface of the third hard carbon active layer through a 50 μm slit die. The wet coating surface density was set to 14.3 g·m⁻², corresponding to a dry solid surface density of 5.0 g·m⁻². The coating was dried at 60℃ and 90℃ for 5 min each, and then vacuum dried at 100℃ for 2 h. The thickness of the sealing layer measured in the cross section was controlled to be 4–7 μm. Under an optical microscope, any 1 mm × 1 mm field of view should be continuously covered by hard carbon and conductive carbon black, and there should be no through holes exposing the third hard carbon active layer.
[0100] After sealing, the negative electrode consists of copper foam, polyacrylonitrile-based carbon cloth, first hard carbon active layer, second hard carbon active layer, third hard carbon active layer and sealing layer from the composite current collector side to the diaphragm side. The first hard carbon active layer is in contact with the polyacrylonitrile-based carbon cloth, and the third hard carbon active layer is in contact with the sealing layer. The porosity of the three hard carbon active layers increases sequentially along this direction and the silver content decreases sequentially. The sealing layer has no silver source coverage on the diaphragm side because no silver source is added in the raw materials.
[0101] The continuity of the cap is detected by combining backscattered electron imaging and surface resistance. Each negative electrode has 500x images collected in seven regions: the center, four corners and two edges. After image segmentation, the continuous hard carbon and conductive carbon coverage area accounts for no less than 99%, and the surface resistance of each of the seven regions is no greater than 80mΩ per block. When any region has a through gap connected to the third hard carbon active layer or the surface resistance exceeds the limit, the negative electrode is marked as having a discontinuous cap and is prohibited from entering the silver content detection.
[0102] To avoid cross-contamination caused by the testing sequence, the test fixture is first installed with a silver-free hard carbon blank and the blank spectrum is acquired. When a silver peak appears on the blank, the sample stage and fixture are cleaned again. After the blank spectrum is qualified, the silver gradient on the cap surface and cross section is tested in sequence. The blank spectrum is reacquired for each batch. The blank spectrum number, sample direction, test point coordinates and original spectrum file path are written into an overwriteable test index record.
[0103] X-ray photoelectron spectroscopy was used to detect the outer surface of the sealing layer membrane. No ion sputtering was performed before testing. The full spectrum was collected at five locations: the center of the negative electrode and two diagonal lines, using an AlKα light source, a 400 μm beam spot, and the same pass power. The percentage of silver atoms was determined according to... calculate, The symbol indicates the percentage of silver atoms on the outer surface of the diaphragm side of the sealing layer, in at%. The symbol represents the integrated intensity of the characteristic peak of silver after subtracting the background, and the unit is count. The symbol represents the relative sensitivity factor of silver in the instrument software and is dimensionless. The symbol represents the index of the discrete element included in the full-spectrum quantitative analysis, ranging from 1 to... Furthermore, because it is only used to identify the order of elements and units are not applicable, The symbol represents the total number of elements involved in quantification. It is a discrete count determined by the set of elements included in the quantification in the current effective full spectrum and is dimensionless. The symbol represents the first The integral intensity of the characteristic peaks of each element after subtracting the background, expressed in counts. The symbol represents the first The relative sensitivity factor of each element is dimensionless;
[0104] The same sensitivity factor library and background subtraction parameters are used for all five positions. If the spectrum of a single position has a charging drift of more than 0.5 eV, a silver peak signal-to-noise ratio of less than 3, or a vacuum degree exceeding the limit during acquisition, the result of that position is marked as invalid and reacquired. The percentage content of silver atoms at all five valid positions should be less than 1 at%, and the maximum value of the five points in the representative batch is 0.42 at%, which is written into the silver detection field on the cap surface.
[0105] Before quantitative X-ray photoelectron spectroscopy, the energy axis and silver peak response are calibrated using a clean silver standard sheet. Detection is allowed when the calibration deviation does not exceed 0.2 eV and the relative standard deviation of the integrated intensity of the standard sheet in three measurements does not exceed 5%. The maximum value of the silver atom percentage at five positions is compared with the 1 at% limit instead of the average value. When the maximum value reaches or exceeds 1 at%, the silver condition of the capping surface is directly written as unsatisfied.
[0106] Cross-sectional silver gradient detection uses the same mosaic cross-section as the S4 layer thickness measurement. Under the same conditions of cross-section, 15kV accelerating voltage, 10mm working distance, 60s acquisition time, and fixed detector dead time, the midpoint of the measured thickness of each of the three hard carbon active layers is used as the energy-dispersive X-ray spectrum sampling position. Five equidistant points are selected along the cross-sectional length for each layer, and the average silver peak count intensity is calculated. , The symbol represents the average count intensity of the silver peak at five sampling points at the midpoint of the first hard carbon active layer, in counts. The symbol represents the average count intensity of the silver peak at five sampling points at the midpoint of the second hard carbon active layer, in counts. The symbol represents the average count intensity of the silver peak at five sampling points at the midpoint of the third hard carbon active layer, in counts.
[0107] The sampling point of the energy dispersive X-ray spectrum must be at least 20% of the measured thickness of any interlayer interface. If the carbon peak count is saturated, the silver peak fitting residual exceeds 5%, or the sampling point falls into a hole, the point is marked as invalid and re-acquired by shifting it 10 μm along the midpoint line of the same layer. The average count intensities of the silver peaks in the three layers of the representative batch are 1280, 690 and 105 respectively. The three values satisfy the relationship of decreasing from the composite current collector side to the diaphragm side and are written into the cross-sectional silver gradient detection field.
[0108] The validity of the cross-sectional silver gradient also requires that the relative standard deviation of the silver peak count intensity of the five valid sampling points in each layer does not exceed 15%. The average count of the first layer, the average count of the second layer, and the average count of the third layer are compared one by one. If the average counts of two adjacent layers are equal, the order is reversed, or there are fewer than five valid points in any layer, the current gradient result is marked as invalid and will not enter the interlocking truth value judgment. After the cross-section is re-prepared, it is re-measured according to the original acceleration voltage, working distance, and acquisition time.
[0109] Pre-lithiation pre-tests were conducted on anodes that passed the sealing and structural inspections and had the same three-layer slurry solid composition, layer thickness, and heat treatment conditions as the anodes to be pre-lithiated. The design capacity of the anode to be pre-lithiated, obtained according to the surface density of the active material and the calibrated specific capacity, was used as the 1C capacity reference. In a three-electrode test fixture, lithium metal was used as the reference electrode and the counter electrode. The temperature was set to -10℃ and the pre-lithiation current was set to 0.1C. The potential of the anode relative to the lithium metal reference electrode and the AC impedance amplitude at 1kHz were recorded every 60s.
[0110] The design capacity is obtained by multiplying the effective area of the negative electrode, the surface density of the hard carbon active material after deducting the current collector and the capping binder, and the first reversible specific capacity calibrated at 25°C and 0.1C for the same batch of hard carbon. The capacity record unit is uniformly mAh. The 1C benchmark is read from the same capacity record for the pre-test and formal pre-lithiation. When the change in the negative electrode cutting area or the surface density of the active material exceeds 2%, the capacity record is regenerated. It is forbidden to use the capacity benchmark of other sizes or other batches of hard carbon.
[0111] The 1kHz impedance of the pre-test uses a 5mV AC disturbance and no additional DC bias is superimposed. The impedance acquisition and potential acquisition use the same clock stamp. The time difference between any two channels does not exceed 1s. The original record includes the sampling number, sampling time, temperature, current, potential, impedance amplitude, instrument range and valid mark. If the sampling interval deviates from 60s by more than 2s, the point and its adjacent rate of change will not participate in the determination of the plateau segment.
[0112] The rate of change of AC impedance at 1 kHz between adjacent sampling times is as follows calculate, The symbol represents the first The rate of continuous impedance change at each sampling time relative to the previous sampling time, in min⁻¹. The symbol represents the first The AC impedance amplitude at 1kHz at each sampling time, in Ω. The symbol represents the AC impedance amplitude at the previous sampling time of 1 kHz, in Ω. The symbol represents the time interval between two adjacent sampling times, in minutes. The symbol represents a discrete sampling index that increases in time and starts from 2. Since it is only used to identify the sampling order and the unit is not applicable, the current rate of change result is recorded as invalid and resampled when the previous impedance amplitude is zero or the instrument is overloaded.
[0113] The impedance change rate threshold was obtained from the first four of five pre-lithiation pre-test specimens from the same batch as a calibration subset: within the impedance change plateau segment determined by the following rules for each specimen, all effective continuous change rates were summarized, and the 95th percentile of the summarized value plus the instrument repeatability margin of 0.0005 min⁻¹ was taken as the upper limit of the continuous change rate of the plateau segment, rounded up to 0.001 min⁻¹. This upper limit was then independently verified using the fifth specimen; in this specific implementation, the 95th percentile of the continuous change rate of the calibration subset plateau segment is 0. 0.0024 min⁻¹, after adding the margin, becomes 0.0029 min⁻¹, rounded up to 0.003 min⁻¹. The threshold is confirmed to be valid if the effective change rate of the fifth test piece plateau segment does not exceed this upper limit (not less than 95%). Otherwise, five test pieces are replaced and the pre-test is repeated. The test piece number, original time series, instrument number, temperature, quantile value, and rounding process used for threshold calculation are all written into the pre-lithiation parameter record. It is forbidden to directly set the maximum value of the sample in the same plateau segment as the threshold and then perform a constant value comparison on that plateau segment.
[0114] The platform segment is determined by sliding a ten-point window in chronological order. First, windows with fewer than ten valid points are deleted. Then, the earliest window with all potentials between 0.15 and 0.30V and impedance amplitude variation coefficient not exceeding 2% is selected as the entry point. Adjacent windows that continuously meet both conditions are then merged. When there are two candidate platform segments with the same starting point, the one with the longer duration is selected. If no platform segment meets the conditions in the entire pre-test, the impedance change rate threshold and the predetermined sampling period are not generated, and the pre-test is repeated.
[0115] The predetermined sampling period was determined independently using five pre-test specimens from the same batch: For each specimen, starting from the first effective rate of change after the platform section entrance, point-by-point enumeration was performed. Only adjacent effective points with potentials between 0.15 and 0.30V and rate of change not exceeding the independent calibration threshold were accumulated. If any condition was not met, the sampling result was invalid, or the sampling interval was interrupted, the accumulation time was reset to zero and restarted from the next effective point. The duration of the section where at least five consecutive effective points appeared for the first time and the subsequent ten effective points did not exceed the limit was taken as the candidate period for that specimen. The maximum value of the five candidate periods was taken and rounded up according to the 1-minute sampling interval as the batch. The predetermined sampling period is used, and the sample with the later starting point is selected when samples are taken in parallel. The minute-by-minute change rate of the representative samples after entering the platform is 0.0048, 0.0039, 0.0032, 0.0029, 0.0027, 0.0025, 0.0024, 0.0022, 0.0022 and 0.0021 min⁻¹. Starting from the 4th point, five consecutive valid points not exceeding 0.003 min⁻¹ are formed for the first time. The maximum value of the candidate period for the five samples is 5 min, so the predetermined sampling period is 5 min. If any sample cannot form the aforementioned section within the platform section, no period is generated and the pre-test is repeated.
[0116] Pre-lithiation of the negative electrode to be pre-lithiated is performed within the range of -10 to 25°C and 0.05 to 0.2C, according to the parameters of the same batch. In this specific implementation, -10°C and 0.1C are continued. The process status is recorded sequentially as not started, in progress, normal completion, abnormal and pending verification, verification failed, or verification passed. When the potential of the negative electrode relative to the lithium metal reference electrode enters the range of 0.15 to 0.30V, and the continuous rate of change of impedance is not greater than the threshold of the same batch and is continuously maintained within the predetermined sampling period of the same batch, the controller terminates the pre-lithiation current and writes the normal completion status. Continuous timing starts from the effective moment when both conditions are met simultaneously for the first time. If any condition fails, exceeds the limit, or the result is invalid, the controller terminates the pre-lithiation current and writes the normal completion status. The sampling interval should be cleared immediately upon interruption; the potential, impedance, temperature, and current channels should all have valid calibration marks; the drift of the reference electrode during the standard checks before and after should not exceed 5mV; the deviation of the measured current relative to the set value should not exceed 2%; if any critical channel is missing or invalid, the reference drift exceeds the limit, the current deviation exceeds the limit for three consecutive sampling points, the temperature exceeds the limit, or the potential exceeds the lower limit of 0.15V, the current should be stopped immediately and the corresponding reason code and abnormal pending review status should be written; the maximum pre-lithiation time should be set to 120min and the maximum cumulative pre-lithiation capacity should be set to 20% of the design capacity; if any upper limit is reached but the common endpoint is still not established, the power should be stopped and the process should proceed to review; continued sampling and discharge waiting are prohibited.
[0117] The interlocking acceptance record for the same batch of negative electrodes shall include at least the three-layer porosity and its valid mark obtained by S4, the average count intensity of the three-layer silver peaks and its valid mark, the maximum value of the percentage content of silver atoms at five points of the capping layer and its valid mark, the pre-lithiation state, the corresponding negative electrode number, the pre-lithiation parameter version, the original time sequence record index, the review conclusion, the calibration status of the testing instrument, the testing personnel, the timestamp, and the retest version. Only when the three-layer porosity increases sequentially from the composite current collector side to the diaphragm side, the three-layer silver peak count intensity decreases sequentially in the same direction, and the percentage content of silver atoms on the outer surface of the diaphragm side of the capping layer is less than 1 at%, and the pre-lithiation state is normally completed or the review is passed, the status shall be written as passed and the batch shall be released into the liquid electrolyte lithium-ion capacitor assembly process.
[0118] The interlocking procedure encodes the three-layer porosity sequence condition, the three-layer silver peak counting sequence condition, and the cap surface silver limit condition into two Boolean fields: a valid flag and a satisfied flag. It also encodes the pre-lithiation state as an independent pre-field. A pass status is generated according to the logical rule that all three valid flags are true, all three satisfied flags are true, and the pre-lithiation state is either normally completed or has passed verification. Statuses that are not started, in progress, pending verification, or have failed verification take precedence over the three structural pass statuses. If any valid flag is false, a test invalidity reason code is generated. If all valid flags are true but one satisfied flag is false, a structural non-compliance reason code is generated, and the reason code is bound to the corresponding original test and pre-lithiation timing index.
[0119] After the status is written, the manufacturing execution system verifies the batch number, quantity, and composite direction mark, and then generates an assembly release number that is only valid for that batch. In abnormal situations, no release number is generated and the material storage location is switched to the isolation area. During retesting, an incremental version number is created without overwriting the previous judgment. The three valid flags and the satisfaction flag are recalculated according to the latest retest version. Assembly release is only restored when the new version meets all the logical conditions again.
[0120] Batch interlocking adopts a batch of 500 negative electrodes as one acceptance batch, and if there are less than 500, they are treated as a complete batch. Porosity and cross-sectional silver gradient are sampled from the first, middle and last positions of the batch. The silver content of the cap surface is obtained from the above three samples. The sampling part number is associated with the production meter standard. If any sampling part causes an abnormal state, the entire acceptance batch is isolated and the average result of other sampling parts is not used to offset it. The retest sample is re-sampled from the front and back sheets adjacent to the abnormal position.
[0121] If any structural condition is not met, the result is missing, or the result is invalid due to the instrument status or sampling position not meeting the requirements, or the pre-lithiation state is not completed normally or passed the verification, the interlocking program writes an abnormal state and stops the batch from entering the assembly process. The abnormal item is retested or verified according to the original sampling conditions, and the original record and retest record are retained. The abnormal state is only lifted when all three structural conditions are retested and all results are valid and met, and the pre-lithiation state is changed to complete normally or passed the verification. Finally, a negative electrode with a continuous silver-free source capping layer, an increasing porosity gradient and a decreasing silver content gradient is obtained, and the pre-lithiation and batch interlocking acceptance are completed. This completes a method for preparing a capacitor battery negative electrode with spatially misaligned electron ion transport paths.
[0122] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
[0123] This invention utilizes the synergistic relationship between composite current collector, three-layer porosity gradient, reverse gradient of carbon-coated silver nanoparticles, and silver-free source capping layer to adjust the distribution of electronically conductive components and the thickness direction position of lithium-ion reachable pore structures, so that the two types of transport paths no longer form unidirectional reinforcement on the membrane side, thereby alleviating the interfacial polarization and surface preferential lithium deposition tendency during low-temperature high-rate charging.
[0124] Furthermore, the pre-lithiation process uses the common endpoint of the negative electrode potential and the 1kHz AC impedance stabilization condition, and the batch acceptance adopts the interlocking judgment of porosity order, cross-sectional silver peak counting order and silver content on the cap surface, so that the prepared negative electrode simultaneously meets the requirements of electrochemical pretreatment state and spatial gradient structure before assembly.
Claims
1. A method for preparing a capacitor battery negative electrode with spatially misaligned electron-ion transport paths, characterized in that, include: S1. Conductive composite of copper foam and polyacrylonitrile-based carbon cloth is formed to create a composite current collector with copper foam as the support and polyacrylonitrile-based carbon cloth as the coating side. S2. Prepare the first hard carbon slurry, the second hard carbon slurry and the third hard carbon slurry respectively, so that the content of pore-forming agent in the three hard carbon slurries increases in sequence and the content of carbon-coated silver nanoparticles decreases in sequence, to obtain a component reverse gradient slurry group. S3. The reverse gradient slurry group of components is coated layer by layer on the polyacrylonitrile-based carbon cloth in the order of the first hard carbon slurry, the second hard carbon slurry and the third hard carbon slurry, and then dried to form a three-layer hard carbon precursor layer. S4. Heat-treat the three-layer hard carbon precursor layer to decompose the pore-forming agent and form a three-layer hard carbon active layer with increasing porosity and decreasing silver content from the composite current collector side to the diaphragm side. S5. A continuous hard carbon and conductive carbon capping layer is formed on the membrane side surface of the three-layer hard carbon active layer without adding silver source in the preparation raw materials, so that the capping layer covers the outer surface of the membrane side of the three-layer hard carbon active layer, and a negative electrode for liquid electrolyte lithium-ion capacitor is obtained.
2. The method for preparing a capacitor battery negative electrode with spatially misaligned electron-ion transport paths according to claim 1, characterized in that, In step S1, the thickness of the copper foam is 50-100 μm, the porosity is 60%-80%, and the pore size is 50-200 μm; the thickness of the polyacrylonitrile-based carbon cloth is 20-40 μm, the areal density is 30-50 g·m⁻², and the areal resistivity is less than 50 mΩ per block; the conductive composite enables the copper foam and the polyacrylonitrile-based carbon cloth to form a continuous surface contact.
3. The method for preparing a capacitor battery negative electrode with spatially misaligned electron-ion transport paths according to claim 1, characterized in that, In step S2, based on the total mass of the solid components of each hard carbon slurry, the mass percentages of ammonium bicarbonate pore-forming agent in the first hard carbon slurry, the second hard carbon slurry, and the third hard carbon slurry are 5%–9%, 10%–14%, and 15%–20%, respectively; and the mass percentages of the carbon-coated silver nanoparticles are 10%, 5%, and 0–1%, respectively.
4. The method for preparing a capacitor battery negative electrode with spatially misaligned electron-ion transport paths according to claim 1, characterized in that, The carbon-coated silver nanoparticles comprise a silver core with a particle size of 30–60 nm and a carbon shell with a thickness of 1–2 nm. The carbon shell coats the silver core and separates the silver core from the liquid electrolyte.
5. The method for preparing a capacitor battery negative electrode with spatially misaligned electron-ion transport paths according to claim 1, characterized in that, In step S3, the coating amount of each of the three coatings is controlled so that the thickness of each hard carbon active layer formed after the heat treatment in step S4 is 25-40 μm.
6. The method for preparing a capacitor battery negative electrode with spatially misaligned electron-ion transport paths according to claim 5, characterized in that, In step S4, the heat treatment temperature is 250°C and the holding time is 2 hours; the three hard carbon active layers formed by the heat treatment have porosities of 25%–35%, 35%–45%, and 45%–55% respectively, in the order from the composite current collector side to the diaphragm side.
7. The method for preparing a capacitor battery negative electrode with spatially misaligned electron-ion transport paths according to claim 4, characterized in that, In step S5, the capping layer is formed of hard carbon and conductive carbon; X-ray photoelectron spectroscopy detection shows that the percentage of silver atoms on the outer surface of the diaphragm side of the capping layer is less than 1 at%; under the same cross section and the same acquisition conditions, the silver peak count intensity of the energy dispersive X-ray spectrum is acquired by taking the midpoint of the measured thickness of each of the three hard carbon active layers as the sampling position, and the silver peak count intensity decreases sequentially from the composite current collector side to the diaphragm side.
8. The method for preparing a capacitor battery negative electrode with spatially misaligned electron-ion transport paths according to claim 7, characterized in that, The three hard carbon active layers are arranged from the composite current collector side to the membrane side in the order of first hard carbon active layer, second hard carbon active layer and third hard carbon active layer; the first hard carbon active layer is in contact with the polyacrylonitrile-based carbon cloth, and the third hard carbon active layer is in contact with the capping layer; the silver content of the first hard carbon active layer, the second hard carbon active layer and the third hard carbon active layer decreases and the porosity increases in sequence.
9. The method for preparing a capacitor battery negative electrode with spatially misaligned electron-ion transport paths according to claim 7, characterized in that, The method also includes using the design capacity of the anode to be pre-lithiated as the 1C capacity reference, and pre-lithiating the anode under conditions of -10 to 25°C and 0.05 to 0.2C; conducting a pre-lithiation test using an anode with the same three-layer slurry solid composition, layer thickness, and heat treatment conditions as the anode to be pre-lithiated; determining the impedance change plateau segment from the 1kHz AC impedance time series data of the pre-lithiation test; determining the upper limit of the continuous change rate within the impedance change plateau segment as the impedance change rate threshold; and determining the shortest continuous sampling duration where the continuous change rate does not exceed the upper limit as the predetermined sampling period; and using the anode's potential relative to the lithium metal reference electrode entering the range of 0.15 to 0.30V, and the continuous change rate of the 1kHz AC impedance not exceeding the impedance change rate threshold and continuing for the predetermined sampling period as the common endpoint for terminating pre-lithiation; the continuous change rate is determined by the absolute value of the difference between the 1kHz AC impedance amplitudes at adjacent sampling times, the 1kHz AC impedance amplitude at the previous sampling time, and the sampling time interval.
10. The method for preparing a capacitor battery negative electrode with spatially misaligned electron-ion transport paths according to claim 7, characterized in that, For the same batch of negative electrodes, interlocking acceptance is performed and a batch acceptance record is generated. Only when all three conditions are met—that the porosity of the three-layer hard carbon active layer increases sequentially from the composite current collector side to the diaphragm side, that the silver peak counting intensity decreases sequentially from the composite current collector side to the diaphragm side, and that the percentage of silver atoms on the outer surface of the diaphragm side of the sealing layer is less than 1 at%—can be effectively detected and all conditions are met, a pass status is written in the batch acceptance record and the batch of negative electrodes is allowed to enter the capacitor assembly process. If any condition is not met, the test result is missing, or the test result is invalid, an abnormal status is written into the batch acceptance record and the negative electrode of that batch is stopped from entering the capacitor assembly process. After re-testing the items corresponding to the abnormal status, the abnormal status will be lifted only when all three conditions are met and all valid test results are obtained.